The Nature of Science in Ontological Studies - Fransistyawan, Rioga; Mukhlis, Mukhlis; Widiastuti, Widia (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
The nature of science has become one of the main themes in philosophical studies, particularly from an ontological perspective. Ontology, as a branch of philosophy that discusses existence and reality, views science as a systematic effort by humans to understand the existing reality. In the ontological framework, science is identified through the existence of the subject of study, the fundamental properties of the reality being examined, and the relationship between the subject (human) and the object being studied. This research is a library study, which means that the research uses library sources such as books, journals, and articles to analyze and support the study of the Nature of Science regarding Ontological Studies. The data analysis used is content analysis. The results of this research indicate that there are 5 schools of thought within the study of ontology that explain the nature of knowledge.